Intermittent Resistance Training at Moderate Altitude: Effects on the Force-Velocity Relationship, Isometric Strength and Muscle Architecture - Morales-Artacho, Antonio J.; Padial, Paulino; García-Ramos, Amador; Pérez-Castilla, Alejandro; Argüelles-Cienfuegos, Javier; De la Fuente, Blanca; Feriche, Belén (Frontiers in Physiology, 2018)
Intermittent hypoxic resistance training (IHRT) may help to maximize the adaptations following resistance training, although conflicting evidence is available. The aim of this study was to explore the influence of moderate altitude on the functional, neural and muscle architecture responses of the quadriceps muscles following a power-oriented IHRT intervention. Twenty-four active males completed two 4-week consecutive training blocks comprising general strengthening exercises (weeks 1–4) and power-oriented resistance training (weeks 5–8). Training sessions were conducted twice a week at moderate altitude (2320 m; IHRT, n = 13) or normoxia (690 m; NT, n = 11). Training intensity during the second training block was set to the individual load corresponding to a barbell mean propulsive velocity of 1 m·s−1. Pre-post assessments, performed under normoxic conditions, comprised quadriceps muscle architecture (thickness, pennation angle and fascicle length), isometric maximal (MVF) and explosive strength, and voluntary muscle activation. Dynamic strength performance was assessed through the force-velocity relationship (F0, V0, P0) and a repeated CMJ test (CMJ15MP). Region-specific muscle thickness changes were observed in both training groups (p < 0.001, ηG2 = 0.02). A small opposite trend in pennation angle changes was observed (ES [90% CI]: −0.33 [−0.65, −0.01] vs. 0.11 [−0.44, 0.6], in the IHRT and NT group, respectively; p = 0.094, ηG2 = 0.02). Both training groups showed similar improvements in MVF (ES: 0.38 [0.20, 0.56] vs. 0.55 [0.29, 0.80], in the IHRT and NT group, respectively; p = 0.645, ηG2 < 0.01), F0 (ES: 0.41 [−0.03, 0.85] vs. 0.52 [0.04, 0.99], in the IHRT and NT group, respectively; p = 0.569, ηG2 < 0.01) and P0 (ES: 0.53 [0.07, 0.98] vs. 0.19 [−0.06, 0.44], in the IHRT and NT group, respectively; p = 0.320, ηG2 < 0.01). No meaningful changes in explosive strength performance were observed. In conclusion, contrary to earlier adverse associations between altitude and resistance-training muscle adaptations, similar anatomical and functional muscle strength responses can be achieved in both environmental conditions. The observed region-specific muscle thickness changes may encourage further research on the potential influence of IHRT on muscle morphological changes.